A municipal database from the 2011 Spanish census. Issue 81 (7th October 2019) - Goerlich, Francisco J.
Abstract : Purpose: The paper aims to describe the process to obtain a complete municipal database from the 2011 Spanish Census information. By complete, the authors mean variables for the full sample of the 8, 116 municipalities as of the census reference date. In addition, the database should be consistent with the public census information released by the National Statistical Institute: microdata and customized tables. Design/methodology/approach: The authors use mainly small area demographic and synthetic estimators that are reconciled using biproportional adjustment (iterative proportional fitting), when needed. Findings: As a result, the authors obtain a complete and consistent municipal database composing 55 variables related to socio-demographic characteristics of persons. Originality/value: The provision of a complete and consistent municipal database, available for download, which is absent in the original 2011 Spanish Census.